2015
DOI: 10.1111/boj.12273
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in Pleurothallidinae (Orchidaceae: Epidendroideae) with an emphasis on the genusAcianthera: chromosome numbers and heterochromatin

Abstract: In this study, we analysed chromosome number variation and chromomycin A3/4′,6‐diamidino‐2‐phenylindole (CMA/DAPI) banding patterns in 48 species belonging to 12 genera of subtribe Pleurothallidinae (Orchidaceae) in order to understand the chromosome evolution based on recent phylogenetic hypotheses and taxonomic treatments. All species had small chromosomes, with numbers ranging from 2n = 20 in two Specklinia spp. to 2n = 80 in an unidentified Octomeria sp. In Acianthera, the most highly represented genus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Symmetric karyotypes are frequent in related group of plants, both among monocots, such as Acianthera (Oliveira et al 2015) and in eudicots, as Rutaceae (Carvalho et al 2005). It is difficult to identify individual chromosomes in those karyotypes or to differentiate the karyotypes of different species of a same genus, and they are generally indicative of primitive karyotypes (Stebbins 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Symmetric karyotypes are frequent in related group of plants, both among monocots, such as Acianthera (Oliveira et al 2015) and in eudicots, as Rutaceae (Carvalho et al 2005). It is difficult to identify individual chromosomes in those karyotypes or to differentiate the karyotypes of different species of a same genus, and they are generally indicative of primitive karyotypes (Stebbins 1971).…”
Section: Discussionmentioning
confidence: 99%
“…They have been used mainly to characterize karyotypes with chromosomes that have the same size and morphology, and to differentiate the karyotypes of species with identical chromosome numbers (see Almeida et al, 2007;Barros e Silva et al, 2010;Cordeiro et al, 2016b;Almeida et al, 2016). The different patterns found can help determine taxonomic distinctions and clarify relationships among species (Carvalho et al, 2005;Almeida et al, 2007;Oliveira et al, 2015), as well as contribute to the description of new taxa, such as Epidendrum sanchezii E.Pessoa & L.P.Felix (Pessoa et al, 2014), Ameroglossum manoel-felixii L.P.Felix & E.M.Almeida (Almeida et al, 2016), and Spondias bahiensis P.Carvalho, Van den Berg and M.Machado (Almeida et al, 2007;Machado et al, 2015). Preliminary studies in the tribe Jacarandeae (Cordeiro et al, 2016b) indicated that heterochromatin distribution appeared to follow a specific pattern (8-16 CMA + terminal bands), while in the tribe Bignonieae (Cordeiro et al, 2017) heterochromatin distribution is quite variable among the species.…”
Section: Introductionmentioning
confidence: 99%
“…Numerically stable species of Citrus L. (Guerra, 1993;Carvalho et al, 2005), Spondias L. (Almeida et al, 2007), and Acianthera Scheidw. (Oliveira et al, 2015), for example, have been karyotypically characterized based on their patterns of CMA/DAPI bands. Although analyses of CMA/DAPI banding patterns have been important in defining species and investigating karyotypic evolution, this technique has not been widely used in the Bignoniaceae.…”
Section: Introductionmentioning
confidence: 99%